Study of Risk Factors for Acute Myocardial Infarction in Western Maharashtra: A Case-Control Study - Tanmay Khindri; Sandeep Narwane; Anup Kharde (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Myocardial infarction (MI) is one of the leading causes of mortality in India. The associated risk factors vary with respect to geographical and cultural difference in patients of MI. Objective: To study the association between known risk factors and MI in patients visiting tertiary rural health care center. Method: The study design was Unmatched Case Control type. Patients of age 18 or above diagnosed of AMI were included as cases. Patients of age 18 or above without prior history of heart disease were included as controls. Pregnant women and patients with coexisting cardiogenic shock, any significant chronic medical illness was excluded. The history of hypertension, Diabetes, family history of CHD, stress in past 1 year, history of alcohol intake, History of tobacco addiction, type of activity at work were recorded. The comparison of case and controls were done using Chi squared test, Fisher's Exact Test and Odds ratio, wherever applicable. A one sided "p" value of <0.05 was considered significant. Results: Of the 230 study participants included in the study, 100(43.5 %) were cases and 130 (56.5%) were Control, respectively. Except for history of stress, there was no statistical difference between number of cases and controls. Conclusion: The known risk factors of MI were not found associated with the disease. There is a need for conduct of study with larger sample size for confirmation of the study results.